Light scattering Q-space analysis of irregularly shaped particles - Heinson, Yuli W.; Maughan, Justin B.; Heinson, William R.; Chakrabarti, Amitabha; Sorensen, Christopher M. (My University, 2015)
We report Q-space analysis of light scattering phase function data for irregularly shaped dust particles and of theoretical model output to describe them. This analysis involves plotting the scattered intensity versus the magnitude of the scattering wave vector q=(4/)sin(/2), where is the optical wavelength and is the scattering angle, on a double-logarithmic plot. In q-space all the particle shapes studied display a scattering pattern which includes a q-independent forward scattering regime; a crossover, Guinier regime when q is near the inverse size; a power law regime; and an enhanced backscattering regime. Power law exponents show a quasi-universal functionality with the internal coupling parameter . The absolute value of the exponents start from 4 when <1, the diffraction limit, and decreases as increases until a constant 1.750.25 when 10. The diffraction limit exponent implies that despite their irregular structures, all the particles studied have mass and surface scaling dimensions of D-m=3 and D-s=2, respectively. This is different from fractal aggregates that have a power law equal to the fractal dimension D-f because D-f=D-m=D-s<3. Spheres have D-m=3 and D-s=2 but do not show a single power law nor the same functionality with . The results presented here imply that Q-space analysis can differentiate between spheres and these two types of irregularly shaped particles. Furthermore, they are applicable to analysis of the contribution of aerosol radiative forcing to climate change and of aerosol remote sensing data.
Citation: Heinson, Y. W., Maughan, J. B., Heinson, W. R., Chakrabarti, A., & Sorensen, C. M. (2016). Light scattering Q-space analysis of irregularly shaped particles. Journal of Geophysical Research-Atmospheres, 121(2), 682-691. doi:10.1002/2015jd024171
Keywords: Light Scattering; Phase Function; Q-Space Analysis; Irregularly Shaped; Particles; Dust Particles